2005
DOI: 10.1002/jcp.20463
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of the differentiation potential of human adipose‐derived adult stem cells

Abstract: Pools of human adipose-derived adult stem (hADAS) cells can exhibit multiple differentiated phenotypes under appropriate in vitro culture conditions. Because adipose tissue is abundant and easily accessible, hADAS cells offer a promising source of cells for tissue engineering and other cell-based therapies. However, it is unclear whether individual hADAS cells can give rise to multiple differentiated phenotypes or whether each phenotype arises from a subset of committed progenitor cells that exists within a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
295
2
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 440 publications
(311 citation statements)
references
References 71 publications
10
295
2
4
Order By: Relevance
“…The concentrations of TGF␤1, TGF␤3, and IGF-1 used for chondrogenic differentiation were based on previous studies of MSCs and ADAS cells (13)(14)(15)17,18,21,(24)(25)(26)(27)(28)30,31). To determine the dose-response effect of BMP-6, the effects of BMP-6 at a range of concentrations (5-500 ng/ml) on the expression of COL1A1, COL2A1, COL10A1, and AGC1 gene transcripts were examined, showing maximum stimulation of COL2A1 and AGC1 and suppression of COL10A1 at 500 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations of TGF␤1, TGF␤3, and IGF-1 used for chondrogenic differentiation were based on previous studies of MSCs and ADAS cells (13)(14)(15)17,18,21,(24)(25)(26)(27)(28)30,31). To determine the dose-response effect of BMP-6, the effects of BMP-6 at a range of concentrations (5-500 ng/ml) on the expression of COL1A1, COL2A1, COL10A1, and AGC1 gene transcripts were examined, showing maximum stimulation of COL2A1 and AGC1 and suppression of COL10A1 at 500 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have confirmed the existence of an abundant and easily accessible source of multipotent stem cells in subcutaneous or intraarticular adipose tissue (13)(14)(15)(16)(17)(18)(19)(20)(21). Cells obtained from adipose tissue have been termed processed lipoaspirate cells, adiposederived adult stromal/stem cells (ADAS cells), or simply adipose-derived stem cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the multipotency of individual cells, ASCs were cultured and ring cloning was performed to select cells derived from one progenitor cell [36]. Forty-five clones were expanded through four passages and then induced for adipogenesis, osteogenesis, chondrogenesis, and neurogenesis using lineage-specific differentiation media.…”
Section: Adipose Tissue As a Source Of Multipotent Adult Stem Cellsmentioning
confidence: 99%